Handbook of Resilience in Children - Goldstein, Sam.; Brooks, Robert B.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2013)
Today’s children face a multitude of pressures, from the everyday challenges of life to the increasing threats of poverty, exploitation, and trauma. Central to growing up successfully is learning to deal with stress, endure hardships, and thrive despite adversity. Resilience – the ability to cope with and overcome life’s difficulties – is a quality that can potentially be nurtured in all young people. The second edition of the Handbook of Resilience in Children updates and expands on its original focus of resilience in children who overcome adversity to include its development in those not considered at risk, leading to better outcomes for all children across the lifespan. Expert contributors examine resilience in relation to environmental stressors, as a phenomenon in child and adolescent disorders, and as a means toward positive adaptation into adulthood. New and revised chapters explore strategies for developing resilience in the family, the therapist’s office, and the school as well as its nurturance in caregivers and teachers. Topics addressed include: Resilience in maltreated children and adults. Resilience and self-control impairment. Relational resilience in young and adolescent girls. Asset-building as an essential component of treatment. Assessment of social and emotional competencies related to resilience. Building resilience through school bullying prevention programs. Large-scale longitudinal studies on resilience. The second edition of the Handbook of Resilience in Children is a must-have reference for researchers, clinicians, allied practitioners and professionals, and graduate students in school and clinical psychology, education, pediatrics, psychiatry, social work, school counseling, and public health.
Preface -- Part I: Overview -- Why Study Resilience; Sam Goldstein, Robert B. Brooks -- Resilience Processes in Development: Four Waves of Research on Positive Adaptation in the Context of Adversity; Margaret O’Dougherty Wright, Ann S. Masten, Angela J. Narayan -- Reconceptualizing  Resilience; Howard B. Kaplan -- Resilience in Gene-Environment Transactions; Zhe Wang, Kirby Deater-Deckard -- Relational Resilience in Girls and Young Females; Judith V. Jordan -- What Can We Learn About Resilience From Large-Scale Longitudinal Studies?; Emmy E. Werner -- Part II: Environmental Issues -- Poverty in Childhood and Adolescence: A Transactional-Ecological Approach to Understanding and Enhancing Resilience in Contexts of Disadvantage and Developmental Risk; Robert D. Felner, Melissa L. DeVries -- Family Violence and Parent Psychopathology: Implications for Children’s Socioemotional Development and Resilience; Sara R. Jaffee -- Understanding and Promoting the Development of Resilience in Families; Susan M. Sheridan, Tara M. Sjuts, Michael J. Coutts -- Resiliency in Maltreated Children and Adults; Shadi Houshyar, Joan Kaufman, Melissa DeVries -- Part III: Resilience as a Phenomenon in Childhood Disorders -- Resilience and the Disruptive Disorders of Childhood; Sam Goldstein, Richard Rider -- From Helplessness to Optimism: The Role of Resilience in Treating and Preventing Depression in Youth; Karen Reivich, Jane E. Gillham, Tara M. Chaplin, Martin E.P. Seligman -- Resilience and Self-Control Impairment; Wai Chen, Eric Taylor -- Part IV: Assessment -- Measuring Resilience in Children: From Theory to Practice; Jack Naglieri, Paul A. LeBuffe, Katherine M. Ross -- Assessment of Social Emotional Competencies Related to Resilience; Jack Naglieri, Paul A. LeBuffe, Valerie Shapiro -- The Resiliency Scales for Children and Adolescents: Constructs, Research and Clinical Application; Sandra Prince-Embury -- Part V: Resilience in the Clinical and School Settings -- Resilience and Positive Youth Development:  A Relational Developmental Systems Model; Richard Lerner, Jennifer P. Agans, Miriam R. Arbeit, Paul A. Chase, Michelle B. Weiner, Kristina L. Schmid, Amy Eva Alberts Warren -- A Resilience Framework for Treating Severe Child Trauma; David A. Crenshaw -- Resilience and the Child with Learning Disabilities; Nicole Ofiesh, Nancy Mather -- Promoting Educational Equity in Disadvantaged Youth: The Role of Resilience and Social-Emotional Learning Building Educational Opportunity; Jazmin A. Reyes, Maurice J. Elias, Sarah J. Parker, Jennifer Rosenblatt -- Resilience through Violence and Bullying Prevention in Schools; Jennifer Taub, Melissa Pearrow -- Caring for the Caregiver: Promoting the Resilience of Teachers; Mary Mackrain, Jennifer L. Fleming, Paul A. LeBuffe -- Enhancing Resilience in Classrooms; Beth Doll -- Creating a Positive School Climate: A Foundation for Resilience; Jonathan Cohen -- Part VI: Shaping the Future of Children and Adults -- Positive Adaptation, Resilience and the Developmental Asset Framework; Arturo Sesman, Jr., Marc Mannes, Peter C. Scales -- The Power of Parenting; Robert B. Brooks -- Building Resilience in Children: A Public Health Approach; Emily B. Winslow, Irwin N. Sandler, Sharlene A. Wolchik, Colleen Carr -- Enhancing the Process of Resilience Through Effective Thinking; Myrna B. Shure, Bonnie Aberson -- Part VII:  Conclusions -- The Future of Children Today; Robert B. Brooks, Sam Goldstein.
Keywords: Child psychology; School psychology; Education; Social work; Psychotherapy; Counseling; Clinical psychology; Child and School Psychology; Education, general; Social Work; Psychotherapy and Counseling; Clinical Psychology